The Impact of the Online Game “Free Fire” on Learning Interest, Learning Achievement, and Aggressive Behavior of Students - Septinarini, S. Muktiwijayanti; Alimuddin, Johar; Tatminingsih, Sri (Edukasi, 2024)
Free Fire Battlegrounds, commonly known as Free Fire, is a popular game among children in Indonesia, as evidenced by previous studies. This game can lead to severe addiction among its users, particularly the younger generation, due to the excitement and curiosity it evokes. This study examines the correlation between Free Fire and students' learning interest, achievement, and aggressive behavior. The research was conducted at SD Negeri Banjaranyar from September to December 2022. The sample consisted of 30 sixth-grade students selected from a total population of 39 using the purposive sampling method. Data collection instruments included field observations, questionnaires, and documentation, and the data were analyzed using the correlational quantitative method. The findings revealed a correlation between Free Fire and students' interest in learning, with a decrease in learning interest corresponding to increased time spent playing the game with a significance value of .007. While learning achievement, measured through test scores, showed a decline in some students, the correlation was not statistically significant on a broader scale. In contrast, aggressive behavior among students tended to rise, with many exhibiting rudeness and frequent use of profanity, likely due to the influence of daily online gaming with a significance value of .004. In conclusion, the study found a correlation between Free Fire and students' learning interest and aggressive behavior, though it has a minimal overall effect on learning achievement. The results of this study can provide a foundation for parents and educators to reduce and manage the potential adverse effects of Free Fire.